Conservation tillage and nutrient management effects on yield of mustard (Brassica juncea L.) and soil properties under pearl millet-mustard cropping system - SHEORAN, HARDEEP SINGH; SHEORAN, SEEMA; ROOHI; PARIHAR, M.D.; KUMAR, AJAY (Journal of Soil and Water Conservation, 2025)
A field experiment was conducted during kharif season of 2021 to find out the impact of tillage and residue management practices on grain and straw yield of mustard (Brassica juncea L.) under pearl milletmustard cropping system. Four tillage and residue management practices i.e., conventional tillage (CT), conventional tillage with crop residue (CTR), zero tillage (ZT) and zero tillage with residue (ZTR) were allocated to main plots and four nutrient management i.e., control, recommended dose of fertilizers (RDF), FYM @ 15 t/ha and 50% RDF + FYM @ 7.5 t/ha were employed in sub-plots. Results revealed that the highest seed yield of mustard was recorded with recommended dose of fertilizers and the extent of increase was from 1.14 to 1.75 t/ha over control. The straw yield also followed the similar trend as that of grain yield. There was significant increase in straw yield of mustard with the application of recommended dose of fertilizers (3.11 to 4.81 t/ha) over control. Moreover, different management practices had no prominent effect on soil bulk density (BD), pH, EC and SOC. However, the zero-tillage practices resulted in a reduction of BD from 1.41 Mg/m3 under CT to 1.38 Mg/m3(ZTR) and 1.39 Mg/m3 (ZT) and the highest SOC was recorded under ZTR treatment (0.55%) and the least was observed under CT (0.5%). Tillage and nutrient management had a significant (p < 0.05) impact on the availability of primary nutrients (N, P, and K) and available nitrogen, phosphorus and potassium (NPK) were recorded significantly higher under ZTR (166.13, 17.08 and 289.83 kg/ha) as compared to CT and ZT. The maximum value pertaining to population of bacteria was observed to be 14.6×106 CFU/g soil in the treatment receiving FYM @ 15 t/ ha under zero tillage with crop residue (ZTR). Similarly, fungi population was significantly increased to 14.7×104 CFU/g soil in comparison to control (5.5×104 CFU/gsoil) whereas actinomycetes population showed an increase from 5.7×102 CFU/g soil to 13.9×102 CFU/g soil under zero tillage with crop residue (ZTR) where FYM was applied@ 15 t/ha as compared to control. Magnitude of dehydrogenase (79 μg TPF/g soil 24/hr) and alkaline phosphatase (129 μg PNP/gsoil/hr) activity was, however, found to be superior under zero tillage practice with crop residue (ZTR) treatment receiving FYM @ 15 t/ha. The results of the study indicated that growing mustard under zero tillage and fertilizer management practices needs time for sustaining yield however on long term basis it could be efficient for obtaining higher yield of mustard while sustaining soil health.